The role of non-coding RNAs in the formation of long-term associative memory after single-trial learning in Lymnaea - Kemenes, György; Benjamin, Paul R.; Kemenes, Ildikó (Frontiers in Behavioral Neuroscience, 2022)
Investigations of the molecular mechanisms of long-term associative memory have revealed key roles for a number of highly evolutionarily conserved molecular pathways in a variety of different vertebrate and invertebrate model systems. One such system is the pond snail Lymnaea stagnalis, in which, like in other systems, the transcription factors CREB1 and CREB2 and the enzyme NOS play essential roles in the consolidation of long-term associative memory. More recently, epigenetic control mechanisms, such as DNA methylation, histone modifications and control of gene expression by non-coding RNAs also have been found to play important roles in all model systems. In this review we will focus on how, in Lymnaea, even a single episode of associative learning can activate CREB and NO dependent cascades due to the training-induced up- or downregulation of the expression levels of recently identified short and long non-coding RNAs.